Les Livres des procurateurs de la nation germanique de l'ancienne Université d'Orléans, 1444-1602 : Quatrième Livre des procurateurs de la nation germanique de l'ancienne Université d'Orléans 1587-1602 : texte des rapports des procurateurs - Ridderikhoff, Cornelia M.; Ridder-Symoens, Hilde de (Education and society in the Middle Ages and Renaissance, 2015)
The fourth register with reports of the presidents of the German Nation of the law University of Orléans for the years 1587-1602 offers a unique account of how students perceived a dramatic period in French and European history.